Improvement in properties of multiwalled carbon nanotube/polypropylene nanocomposites through homogeneous dispersion with the aid of surfactants - Cheng, Henry Kuo Feng (2013)
The effects of different surfactants on the properties of multiwalled carbon nanotubes/polypropylene (MWCNT/PP) nanocomposites prepared by a melt mixing method have been investigated. Sodium dodecyl sulfate (SDS) and sodium dodecylbenzene sulfonate (NaDDBS) were used as a means of noncovalent functionalization of MWCNTs to help them to be dispersed uniformly into the PP matrix. The effects of these surfactant-treated MWCNTs on morphological, rheological, thermal, crystalline, mechanical, and electrical properties of MWCNT/PP composites were studied using field emission scanning electron microscopy, optical microscopy, rheometry, tensile, and electrical conductivity tests. It was found that the surfactant-treatment and micromixing resulted in a great improvement in the state of dispersion of MWCNTs in the polymer matrix, leading to a significant enhancement of Young's modulus and tensile strength of the composites. For example, with the addition of only 2 wt % of SDS-treated and NaDDBS-treated MWCNTs, the Young's modulus of PP increased by 61.1 and 86.1%, respectively.